The role musical preferences play in the modulation of emotions for people with mental disorders. (February 2016) - Gebhardt, Stefan; Kunkel, Markus; von Georgi, Richard
Highlights: People with mental disorders use music for the reduction of negative emotions. The preference of reflexive and complex music (classical music/jazz) is mostly preferred by people with personality disorders. The preference of reflexive and complex music (classical music/jazz) is used less for fun stimulation than in healthy individuals. Musical preferences are linked to specific patterns of emotion modulation in mental disorders. The knowledge of the role of music preferences has a special impact on music therapy and psychotherapy. Abstract: The objective of this study was to explore the relationship between the use of music in everyday life for the modulation of emotions and musical preferences, focussing on people with mental disorders. Musical preferences were assessed in the population of a psychiatric hospital according to different musical preference categories. The IAAM (inventory for the assessment of activation and arousal modulation through music) measured the situation-dependent use of music in everyday life. Data were compared to a healthy control population. The results indicated that people with mental disorders used music for the reduction of emotions with negative valence. This was especially true for those individuals who preferred reflective and complex music (such as classical music). These participants primarily had diagnoses of personality disorders, and they used music less for fun than healthy comparators. Connections between musical preferences and emotional modulation patterns in the use of music in everyday life were much more differentiated in the general population than in the psychiatric cohort. Further studies on the basis of this empirical approach are warranted.